Jordförvärvslagens ändring 2005 och dess påverkan vid skogsfastighetsköp : The amendment of Lad Acquisition Act 2005 and its influence on forest property purchase - Nilsson, Sara (SLU/School for Forest Management, 2011)
Since the beginning of the 1900s Sweden has had laws and rules governing the ownership of agricultural and forest land. The foundations of the current Land Ownership Law, “Jordförvärvslagen 1979:230(JFL)”, are from 1979. The most recent review and adaptation of the law occurred in 2005. Its main purpose is to prevent a passive ownership of land in Sweden and to ensure that the land is actively worked. The law is also used as a regional political tool to encourage business and development in rural areas. An important term in the Law is “glesbygd”, sparsely populated area. “Glesbygd” is a general term for councils and parishes in Sweden with low population densities. Areas defined as “glesbyd” can be found in “Jordförvärvsförordningen(JFF)”. JFL is applicable to both corporations and individual people. The aim of this dissertation is to examine whether adaptions to JFL in 2005 changed the circumstances for private people who wish to acquire agricultural or forest land and if this led to changes in property prices. The study is restricted to 4 counties; Västernorrland, Jämtland, Västerbotten and Norrbotten. Corporate and executive acquisitions are not discussed within this dissertation. The dissertation focuses on forest properties. Hypotheses:  The number of declined applications for permission to purchase land varies between the studied counties.  Forest properties that require approval through JFL attract fewer buyers leading to lower prices.  The anxiety felt by potential buyers is not proportional the number of declined applications for purchase of land. A literature study was carried out of JFL, the laws development and interpretation. Data concerning permission for land purchase applications was collected from the Swedish Board of Agriculture, selling prices for properties were available through LRF Konsult. Interviews of potential buyers concerning their knowledge about JFL and applications for purchase permits were carried out. The result shows that the number of applications for purchase permits made by private people between 2003 and 2008, in the northern counties, has increased from 342 to 693 per year. Prior to the 1st of July 2005, the purchaser was able to agree to a commitment to inhabit the property within 6 months after purchase. When including these purchasers, applications have increased from 441 to 693 per year. Within the counties of Norrbotten and Västernorrland, no denials for applications for purchase permits, made by private people, were found between 2003 and 2008. Within Västerbotten denials for applications for permits could be found for each year. At most, 8,6% of applications were denied(2004). On average, Västerbotten had a denial percentage of 3,75% over the studied period. In comparison Jämtland had a denial percentage of 0,81%, with no denials registered during 2005 and 2008. Jämtland had the highest rate of denials during 2007 with 2,02%. During the studied period, prices of properties without inhabitable buildings within sparsely populated areas (glesbygd) increased more than properties outside these areas. With an index of 1,0 applied to 2003 property prices within “glesbygd” areas and outside of “glesbygd” areas, the 2008 prices gave an index of 2,17 and 2,03 respectively. The strongest price increases within sparsely populated areas occur after 2005. Between 2003 and 2005 price increases for within “glesbygd” areas and 2 outside of “glesbygd” areas are comparatively even. The interview enquiries showed that a large number of the participants are aware of JFL existence. Knowledge of when purchase permits are required and the possibilities to be granted a permit is less predominant. 50% of participants believe that they have a small to reasonable chance of being granted a permit. 50% also believe that interest in agricultural properties within sparsely populated areas would be greater if JFL did not regulate purchases by private people. 9 of 22 believed that property sellers would rather sell to those that are not required to apply for purchase permits. The aim of the adaptations to JFL in 2005 was to strengthen the law. From the increase in the number of permit applications that occurred from 2005 onwards, I conclude that the result of changes to JFL has not given the desired effect. Neither has the law, or the presumed effect of the changes to it, dampened the increase in price of forest properties. It was not possible to determine the number of permit applications from people who live in neighbouring municipalities, other areas of the county or who come from other countries. In today’s society where we work, study and live can be spread out over large geographical areas. It would be interesting to know how many applicants, despite having been registered for less than 12 months within the municipality where they have purchased property, consider themselves as residents of the municipality. Another conclusion from this study is that JFL is interpreted differently between counties; the number of denied applications relative to the total number of applications varies considerably between counties. JFL is well known among those who are interested in buying forest properties in Norrland. Knowledge of when a purchase permit is required and the chances of being granted a permit is however weaker and often incorrect. I believe that JFLs strict regulation during the 80s continues to have an effect on potential buyers in the form of an unjustified amount of anxiety. More access to information about today’s JFL would be appropriate. If the intention is that JFL should be an instrument for governing the ownership and use of land in sparsely populated areas, I believe that another form of land government would be more effective.